2015
DOI: 10.1038/ncomms8980
|View full text |Cite
|
Sign up to set email alerts
|

Geographic range did not confer resilience to extinction in terrestrial vertebrates at the end-Triassic crisis

Abstract: Rates of extinction vary greatly through geological time, with losses particularly concentrated in mass extinctions. Species duration at other times varies greatly, but the reasons for this are unclear. Geographical range correlates with lineage duration amongst marine invertebrates, but it is less clear how far this generality extends to other groups in other habitats. It is also unclear whether a wide geographical distribution makes groups more likely to survive mass extinctions. Here we test for extinction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 67 publications
3
33
1
Order By: Relevance
“…Alternatively, perhaps there truly was no selection acting on these traits. It is possible that other characteristics were influential, such as geographical range size, but previous studies of terrestrial vertebrates during the Triassic–Jurassic mass extinction have suggested this is not the case (Dunhill & Wills ). Our finding of phylogenetic clustering of extinction in the Archosauromorpha might be a result of sampling bias rather than selective extinction (Soul & Friedman ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, perhaps there truly was no selection acting on these traits. It is possible that other characteristics were influential, such as geographical range size, but previous studies of terrestrial vertebrates during the Triassic–Jurassic mass extinction have suggested this is not the case (Dunhill & Wills ). Our finding of phylogenetic clustering of extinction in the Archosauromorpha might be a result of sampling bias rather than selective extinction (Soul & Friedman ).…”
Section: Discussionmentioning
confidence: 99%
“…Geographical factors such as range size and occupied latitude have also been suggested, as these traits may influence survival during spatially heterogeneous disturbances (Erwin ; Powell ; Jablonski ). However, some authors have suggested that few, if any, traits reduce extinction risk during mass extinctions (Jablonski ; Dunhill & Wills ). In addition, most of these studies have focused on marine taxa, and extinction selectivity in the terrestrial realm in deep time has only recently come under investigation.…”
mentioning
confidence: 99%
“…All the novel network models show a cosmopolitan distribution of dinosaurian taxa through the Triassic, Jurassic and Early Cretaceous, albeit one that is obscured by variation in spatiotemporal sampling intensity. The widely accepted poorly sampled Middle Jurassic and early-Late Cretaceous (Wang & Dodson, 2006;Barrett et al, 2009;Upchurch et al, 2011;Benson et al, 2013;Stubbs et al, 2013;Dunhill & Wills, 2015;Starrfelt & Liow, 2015) time bins stand out as periods of apparent low biogeographical connectivity in all the network models. The first-step models echo the novel connection network 'cosmopolitanism' up until the earliest Cretaceous, a result that is consistent with other studies (Ezcurra & Agnolin, 2012a), before we see a sharp decline in the number of 'first steps' leading into the Aptian-Albian.…”
Section: Discussionmentioning
confidence: 99%
“…This concern can be 271 manifold, but the two most pertinent issues here involve incomplete sampling and/or issues of 272 stratigraphic bias. While it is important to be aware of the fact that the fossil record is 273 incomplete, it is worth recognizing that there is a large body of research that demonstrates that 274 many of the biogeographic patterns preserved in the fossil record, particularly in marine settings, 275 represent real biological phenomena, rather than taphonomic artifacts (Myers & Lieberman, 276 2011;Rook, Heim, & Marcot, 2013;Dunhill & Wills, 2015), although that does not mean that 277 such artifacts played no role in this study. Further, it is also prudent to realize that sampling bias 278 is a common issue in studies of extant biodiversity and species distribution, and much work 279 needs to be done in this area to alleviate the biases of the extant biota (Lieberman, 2002; 280 Carrasco, 2013).…”
mentioning
confidence: 98%